Chlorophyll “a” fluorescence of Zea mays L. (maize) cultivars that differs in degree of their drought tolerance: Targets locked - Amir, Misbah; Bashir, Nahidah; Afzal, Shehrooz; Athar, Habib-ur-Rehman; Zafar, Zaffar Ullah; Mahmood, Seema; Ogbaga, Chukwuma Chucks; Kashif, Ali Sher; Inqalabi, Talou e Islam; Ayyaz, Ahsan; Rasheed, Iqra; Asghar, Zahida; et al. (Journal of Cereal Research, 2022)
The research was conducted to check the photosynthetic activity of three maize (Zea mays L.) cultivars (DTC, EV78 and 6621) by OJIP chlorophyll a fluorescence and gas exchange parameters under drought/water stressed conditions. Water potential of leaf was decreased in Zea mays L. cultivars induced stomatal closure and reduced CO2 influx. Among cultivars, DTC had greater water use efficiency (WUE) and photosynthetic rate. Higher PSII and PSI quantum efficiency and chlorophyll contents were also observed in DTC cultivar relative to EV-78 and 6621 cultivar. The (JIP) analysis from fast chlorophyll a kinetic estimation elucidated acclimatory processes in cultivar DTC. A greater protection of reaction centers which involved the conversion of absorbed energy into electron transport (ET0/RC) and remainder absorbed energy was safely dissipated (DI/RC) in DTC. Fluorescence differential kinetics revealed that there was greater energetic connectivity among antenna pigments and reaction center in DTC unlike cv. EV78 and cv.6621 where L-band appeared. Kinetics difference at 3 ms showed that cv. DTC had a lower K band appearance which indicated that oxygen evolving complex remained more intact and there was more functional PSII in DTC relative to the other maize cultivars. Thus, DTC showed the highest drought tolerance potential in terms of stability and efficiency of PSII and PSI followed by EV 78 while cultivar 6621 was the least drought tolerant. However, cyclic electron flow was apparently higher in 6621 compared with the others suggesting a greater damage to PSII in 6621 but active PSI. Our findings are discussed in relation to crop yield.